PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR SISWA PADA TEMA 8 SUBTEMA 1 PADA KELAS V UPTD SDN 124388 SIANTAR MARTOBA - Purba, Vani; Purba, Natalina; Sitohang, Sukardo (Pendidikan Bahasa Indonesia dan Sastra (PENDISTRA), 2023)
ABSTRACT This study aims to determine the effect of the contextual teaching and learning model on student learning outcomes in theme 8 sub-themes 1 in class V UPTD SDN 124388 Siantar Martoba. There are 2 hypotheses in this study, namely: (ha) there is an influence of the contextual teaching and learning model on student learning outcomes in theme 8 sub-theme 1 in class V UPTD SDN 124388 Siantar Martoba and (Ho) there is no effect of the contextual teaching and learning model on student learning outcomes on theme 8 sub-theme 1 in class V UPTD SDN 124388 Siantar Martoba. This research was carried out in the 2022/2023 academic year. This research method is an experiment with a pre-experimental research design with a One-Group Pretest-Posttes Design research design. The sample of this research was 36 students consisting of 19 male students and 17 female students. Data collection techniques used are observation, documentation and tests. The data is processed using statistical analysis techniques. From the results of data analysis, it was found that tcount = 16.40 and ttable = 1.68 so that it can be concluded that tcount > ttable, so there is an influence of the contextual teaching and learning model on student learning outcomes in theme 8 sub-theme 1 in class V UPTD SDN 124388 Siantar Martoba . This means Ha = accepted and Ho = rejected.